Postpartum Pneumomediastinum: An Uncommon Cause for Chest Pain - Revicky, Vladimir (Hindawi Publishing Corporation, 2010)
This case report refers to a 32-year-old primiparous woman with a mild asthma, who had a normal vaginal delivery in a birthing pool and developed an acute postpartum chest pain due to pneumomediastinum and subcutaneous chest emphysema. After 72 hours of observation, she was discharged home without any residual symptoms.